(untitled) - DZI – Deutsches Zentralinstitut für soziale Fragen und die Senatsverwaltung für Integration, Arbeit und Soziales des Landes Berlin (Soziale Arbeit, 2010)
Soziale Arbeit, founded in 1951, is an independent academic journal which addresses developments in the context of social work. It is one of the most important publication media in its field and is read by teachers, students and researchers in social work and social pedagogy as well as by professionals and managers from associations and institutions. The journal’s aim is to promote professional development in social work fields by presenting methods and new concepts, in addition to subject-specific practical reports. In the ‘Rundschau’ (Review) section, information from all social fields is compiled. The ‘Tagungskalender’ (Conference Calendar) refers to important events, and the ‘Zeitschriftenbibliographie’ (Bibliography of Journals) lists current articles from professional journals. Soziale Arbeit is published 11 times a year with an annual focus issue published as a double issue. All scholarly articles submitted for publication in the journal undergo a double-blind peer review process. The editorial board is supported in an advisory capacity by a professional advisory board consisting of individuals from associations, universities, politics and administrative bodies. The journal cooperates with the academic societies of social work from Germany (DGSA) and Austria (OGSA). All social work contributions are indexed in the literature database DZI SoLit.